Analysis of Referral SOP Implementation and Pre-Referral Communication of the National Health Insurance System at Sabutung Health Center, Pangkajene Regency and Islands - Istiqamah, Nurul Fajriah (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2023)
Obstacles in referring inpatient BPJS Health patients to the hospital must first confirm and wait for an empty room, until a patient has to be given a referral out of town on the grounds that the hospital room is full. This results in patients waiting and slow to get medical services. The type of research that will be used is qualitative research with a phenomenological approach. Results: Based on the studies that have been carried out, it is known that the Sabutung Health Center is not suitable, namely preparing referrals for patients by giving patients and or their families explanations in a language that the patient/family understands, and informed consent as part of an operational procedure that is closely related to the technical procedures for patient care. Conclusion: According to the SOP informant, the Sabutung Health Center already exists, and has made pre-referral communication via telephone, but has not reconfirmed with the referral health facility when they want to refer patients